Board bias, information, and investment efficiency - Martin Gregor; Beatrice Michaeli (Charles University in Prague, Institute of Economic Studies (IES), 2024)
We study how interest alignment between CEOs and corporate boards influences investment efficiency and identify a novel force behind the benefit of misaligned preferences. Our model entails a CEO who encounters a project, gathers investment-relevant information, and decides whether or not to present the project implementation for approval by a sequentially rational board of directors. The CEO may be able to strategically choose the properties of the collected information—this happens, for instance, if the project is ''novel" in the sense that it explores new technology, business concept, or market and directors are less knowledgeable about it. We find that only sufficiently conservative and expansion-cautious directors can discipline the CEO's empire-building tendency and opportunistic information collection. Such directors, however, underinvest in projects that are not novel. From the shareholders' perspective, the board that maximizes firm value is either conservative or neutral (has interests aligned with those of the shareholders) and always overinvests in innovations. Boards with greater expertise are more likely to be conservative, but their bias is less severe. Our analysis shows that board's commitment power and bias are substitutes.
Keywords: D83; D86; G30; G31; G34; 330; Empire-building; biased board; underinvestment; overinvestment; endogenous information